The social construction of 'capacity building': a grounded theory study of organisation development consultants' accounts - Eagar, Ryan (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
The primary aim of this thesis is to explore, through organisation development (OD) consultants' accounts, the meaning of 'capacity building' in the South African development context. The need for theory development in this area is apparent from two interrelated vantage points. Firstly, while 'capacity building' is an increasingly espoused development approach, it is seen to be a confusing and ill-defined concept, for which there exists no adequate theory. Secondly, there is an growing call within the OD field to perfonn 'recOIlllaissance' (Weick,1990) on OD as it is being practised in different socio-historical and organisational contexts, so as to discern future trends for this discipline. Due to the lack of documented debate which grounds OD issues in the South African development sector, OD practitioners' 'capacity building' interventions were seen to provide suitably unchartered terrain for this study. Given that theory generation was intended, the general epistemological principles provided by Glaser and Strauss's (1967) 'grounded theory' methodology were adopted. As a way of avoiding some of the criticisms and limitations of this approach, this thesis followed later conceptualisations of this method, in particular its reframing within the social constructionist idiom. In accordance with this perspective, this study directed attention to the ways in which OD consultants, in a non-governmental organisational (NGO) sector known as 'intermediary' NGOs, accounted for their 'capacity building' role in this development context. The results, based on in-depth interviews with ten OD consultants, indicate that 'capacity building' is an elusive and inchoate concept with more than one meaning for the participants. Their narrative account variously constructs 'capacity building' as value-driven OD process facilitation; funder and market regulated service provision; and people-driven product delivery. As a result of this multi-vocal construction, the participants' accounts reveal that OD consultancy in this sector is primarily concerned with 'managing the tensions' of the consultants' ambiguous and contradictory roles. By examining how the tensions articulated by the consultants inhere in their relationship to the environment in which they operate, this thesis firstly explores how the contradiction and anlbiguity attached to this concept can be traced to different stakeholder expectations of 'capacity building'. Secondly, it exanlines how these different stakeholder discourses conflict with each other and with an OD perspective. Thirdly, through an explication of the core category of 'managing tensions', it explores the image of OD consulting as a 'shifting and inconstant balancing act'. Fourthly, it shows how there exist wider contextual forces operating in the development sector which serve to throw these consultants 'off balance' and into delimited and 'received' service provision roles which run counter to their raison d'etre. Finally, the research examines new ways of approaching the 'capacity building' question and of understanding the nature of OD consultancy. It concludes with an attempt to respond to a conceptual aporia in OD literature by examining possible alternative images and metaphors for the role of the OD consultant.
Keywords: Organizational change -- South Africa; Business consultants -- South Africa